Pengaruh Inovasi Produk Dan Pemasaran Media Facebook Terhadap Minat Beli Batik Pada UD. Silvia Desa Telaga Biru-Tanjung Bumi - Endah Sofy Tri Pamungkas; Bambang Setyo Pambudi (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
Tanjung Bumi batik has a rich variety of motifs, patterns, and colors that can describe the character of the coastal population, especially Madura Island. The purpose of this study was to determine whether product innovation and Facebook media marketing had an effect on buying interest in batik. The sampling technique in this study used the non-probability sampling method with purposive sampling technique, and analyzed with IBM SPSS 2.0 software. The results of this study indicate that the product innovation variable (X1) is worth 0.608, which shows a value of 0.000 0.05, this indicates that the product innovation variable has a significant effect on buying interest. The Facebook media marketing variable (X2) has a value of 0.424, which shows a value of 0.000 0.05, it shows that the Facebook media marketing variable has a significant effect on buying interest. Based on testing the value of Ftable 2.41 Fcount of 483.646 with a significance of 0.000 0.05, this shows that Product Innovation and Facebook Media Marketing have a simultaneous or joint effect on buying interest.